PENGARUH METODE BERNYANYI TERHADAP KETERAMPILAN BERBICARA PADA PEMBELAJARAN BAHASA INDONESIA KELAS 1 SDN 125 PALEMBANG - Tesalonika Br Tarigan; Nora Surmilasari; Dian Nuzulia A, R (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the singing method on the speaking skills of class 1 students of SDN 125 Palembang. This study uses a quantitative approach using an experimental method and a Posttest-only control design type. The population in this study was 110 students consisting of class IA with 28 students, IB with 28 students, IC with 27 students and class ID with 27 students. In this study, 2 classes were used for sampling using Random Sampling, namely class IC and class ID. The data collection technique used was testing and documentation. The data analysis technique used was the t-test with the help of SPSS version 26. The posttest of the control class was 0.080> 0.05 and the significant value of the posttest of the experimental class was 0.088> 0.05 or it can be concluded that the data can be stated as normally distributed. Based on the results of the hypothesis calculation, it was found that the t-count value for the control class and the experimental class was 4.402 with the t-table value obtained being 1.675 with df = n - 2 then df = 54 - 2 = 52 so df = 52. So it can be concluded that the t-count value of 4.402> t-table 1.675 thus H0 is rejected and Ha is accepted or there is an influence of the singing method on the speaking skills of class 1 students of SD Negeri 125 Palembang